The 1995 Chicago heat wave : mitigating damage in unexpected disasters - Thompson, Kenneth R. (London : SAGE Publications: SAGE Business Cases Originals, 2021)
Depending upon different accounts, the 1995 Chicago Heat Wave led to the deaths of between 600 and 700 people. This case will provide a day-to-day review of the events of eight days central to the disaster, comments from first responders and community leaders as events unfolded, and review of two key reports that followed with their recommendations, which were to mitigate the effect of this and similar events in the future through changing processes, attitudes, and improving preparation. Parallels from this disaster to the United States' response to the COVID-19 pandemic will be considered. The major learning goal in the case is to develop students' ability to consider more critical "what if scenarios" as a means to be prepared for the unexpected, by thinking of plans that could have been made in advance of the Chicago Heat Wave disaster.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Emergency management; Heat waves (Meteorology) -- Economic aspects -- Illinois -- Chicago